Analisis Keterampilan Pengelolaan Kelas Dengan penerapan karakter peduli oleh Guru Pendidikan Agama Kristen di SD Negeri Kelaisi II - Adolfina Oualeng; Delila Tanaem; Halena M. Bekata (Peneliti.net, 2021)
Building awareness of students is a difficult way to manage a class if the teacher does not understand the development of students. The purpose of this study was to obtain the results of the analysis of how classroom management skills are carried out by Christian Religious Education teachers by developing caring relationships with students. The results showed that by developing a caring relationship with students, a friendly atmosphere can be created, two-way communication between teachers and students can be created, but there is also a good relationship between teachers and parents, but this good relationship is also not accompanied by proper discipline. so that the awareness of students to obey is still lacking.